The efficacy of immediate and delayed corrective feedback in the correct use of English definite and indefinite articles - Soori, Afshin; Abd. Samad, Arshad (Marsland Press, 2011)
The process of giving effective feedback is a central concern for teachers and researchers in both first language and second language writing. Many teachers correct students’ written errors in the hope that this will help them improve the students’ mastery over the correct use of targeted linguistic forms, while Truscott (1996) considered this approach as a misguided endeavour due to his claim that feedback on grammar errors had no place in writing classrooms and it should be abandoned. Regarding this issue, the current study investigated the results of nine weeks treatment on the efficacy of immediate and delayed corrective feedback in the correct use of definite and indefinite articles. Data were collected from a sample of 51 (34 males and 17 females) first year Iranian EFL medical students. The students were administered three rational cloze tests (pre-test, immediate post-test, and delayed post-test). The finding of the study revealed that immediate corrective feedback had a significant effect on the correct use of English articles and the students received corrective feedback significantly improved their ability in using English article system correctly and that they retained this ability when they were given a new test four weeks after the treatment session. This study also indicated that there was a change in article scores across the three different time periods. Thus, the main effect for time was significant.